1998
DOI: 10.1016/s0895-7061(97)00401-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Basal Sympathetic Tone and α1-Adrenergic Responsiveness in Association With the Hypotensive Effect of Melatonin in Spontaneously Hypertensive Rats

Abstract: Early investigations have suggested a relationship between hypertension and melatonin, a pineal hormone. The aims of this study were to evaluate the implication of the sympathetic nervous system in the acute effect of melatonin on blood pressure in conscious 12-week-old spontaneously hypertensive rats (SHR) and Wistar-Kyoto rats (WKY), and to determine whether the hypotensive effect of melatonin is associated with alterations in pre- or postsynaptic mechanisms. Melatonin, 10 mg/kg, produced a sustained time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 21 publications
0
55
0
1
Order By: Relevance
“…Spontaneously hypertensive rats (the animal model of arterial hypertension with the increased activity of the sympathetic system) are more sensitive to melatonin than are transgenic rats, TGR(mRen-2)27, with an upregulated renin-angiotensin-aldosterone system. 22 In our study, the etiology of arterial hypertension, which was present in the case of some patients, was also not known, but the differences in reaction to melatonin supplementation suggest that the group was not homogenous in this respect. Similar to our previous publication, no relationship was found between the effect of melatonin supplementation and the presence or accumulation of classical risk factors of ischemic heart disease nor between the kind of pharmacological treatment used.…”
Section: Study Limitationsmentioning
confidence: 62%
“…Spontaneously hypertensive rats (the animal model of arterial hypertension with the increased activity of the sympathetic system) are more sensitive to melatonin than are transgenic rats, TGR(mRen-2)27, with an upregulated renin-angiotensin-aldosterone system. 22 In our study, the etiology of arterial hypertension, which was present in the case of some patients, was also not known, but the differences in reaction to melatonin supplementation suggest that the group was not homogenous in this respect. Similar to our previous publication, no relationship was found between the effect of melatonin supplementation and the presence or accumulation of classical risk factors of ischemic heart disease nor between the kind of pharmacological treatment used.…”
Section: Study Limitationsmentioning
confidence: 62%
“…Mechanisms possibly involved include a direct hypothalamic effect, a decrease in catecholamine levels, as well as relaxation of the aortic smooth muscle wall. 39,40 Similarly, in hypertensive rats, Pycnogenol dose-dependently decreased systolic blood pressure after intravenous injection. In a double-blind, placebo-controlled, crossover study in hypertensive patients, oral administration of Pycnogenol reduced slightly elevated systolic blood pressure to normal values.…”
Section: Immunohistochemical Studies For Mmp2 Bax Inos and Cox-2mentioning
confidence: 95%
“…It had been concluded that the hypotensive effect of melatonin in rats may be mediated by its anti-oxidative effect rather than its receptor . As reported previously, melatonin decreases plasma renin and serum norepinephrine concentrations (K-Laflamme et al, 1998). The improved NO production and decrease oxidative load after melatonin administration may lead to BP reduction (Girouard et al, 2001).…”
Section: Discussionmentioning
confidence: 64%